252. Relative Use of Carbapenems in Immunocompromised Patients. (26th November 2018) - Pierce, Jacob; Lee, Kimberly; Markley, John; Pakyz, Amy; Doll, Michelle; Kirk, Andrew; Bearman, Gonzalo; Cruz, Oveimar De La; Stevens, Michael
Abstract: Background: Gram-negative bacterial infections are associated with high mortality in immunocompromised hosts, and the presence of drug resistance further increases mortality. Antibiotic consumption is a key outcome measure for Antimicrobial Stewardship Programs. Proper utilization of antibiotics can help limit the development of antimicrobial resistance. Resistance in Gram-negative organisms such as Pseudomonas, Enterobacter, and Acinetobacter is a major issue given the paucity of new drugs in the antibiotic pipeline for these organisms. A novel relative carbapenem consumption metric (the Proportion of Carbapenem Consumption, or PoCC) was recently described in US academic medical centers. The PoCC is calculated as follows: PoCC = [(meropenem Days of therapy(DOT)/1, 000 patient-days (PDs))/(meropenem DOT/1, 000 PDs + cefepime DOT/1, 000 PDs + piperacillin–tazobactam DOT/1, 000 PDs)]. The regional mean PoCC for the South Atlantic region has previously been approximated at 17%. Methods: We examined the PoCC for the Bone Marrow Transplant (BMT) and dedicated Hematology/Oncology (H/O) inpatient wards at an academic medical center from August 2012 to June 2017. Results: Conclusion: This is the first description of the PoCC metric for dedicated Hematology/Oncology and Bone Marrow Transplant wards. When compared with national and regional mean PoCC scores for academic medical centers, the PoCC for these units was higher. More research is needed to determine the optimal PoCC scores for these types of units. The PoCC can contextualize relative carbapenem use and may be a useful antibiotic consumption metric. However, it does not provide data on absolute consumption. Further studies are needed to determine the best use of the PoCC metric by Antimicrobial Stewardship Programs for Hematology/Oncology and Bone Marrow Transplant wards. Disclosures: All authors: No reported disclosures.